Evaluate China's current soft power strategy - Dem, Tithsatya (Technium Social Sciences Journal, 2023)
Soft power strategy is an important aspect of China’s foreign diplomacy. It must adapt to China’s global peaceful rise. It must create understanding, respect and ultimately support China’s political models and policies. Then, it will help China win friends’ hearts and minds around the world. Therefore, it is not surprising that building and predicting a soft power strategy is firmly on China’s international agenda. This paper starts with the background of soft power and then describes the rises and the limitations of China’s current soft power strategy by using documents from previous researches and social media. Finally, the paper illustrates suggestions and solutions to improve this charming strategy.